2014
DOI: 10.1016/j.jtcvs.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Single center experience with the Sorin Bicarbon prosthesis: A 17-year clinical follow-up

Abstract: The SBP has shown excellent results in terms of clinical improvement and freedom from valve-related complications, even up to 17 years after AVR and MVR. It therefore seems to be a safe option whenever a mechanical prosthesis is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…This prosthesis has been in clinical use since 1990 and has shown remarkable long-term results 14 . As reported by Celiento and co-workers in their 17-year follow-up study “a low incidence of embolic events was observed with a linearized rate of 0.39% ± 0.09%/patient-years after AVR” 15 . These outcomes are consistent with those disclosed by Azarnoush et al .…”
Section: Discussionmentioning
confidence: 71%
“…This prosthesis has been in clinical use since 1990 and has shown remarkable long-term results 14 . As reported by Celiento and co-workers in their 17-year follow-up study “a low incidence of embolic events was observed with a linearized rate of 0.39% ± 0.09%/patient-years after AVR” 15 . These outcomes are consistent with those disclosed by Azarnoush et al .…”
Section: Discussionmentioning
confidence: 71%
“…A group in Italy recently published 17 year follow-up from a cohort of 507 patients with Sorin mechanical valves. 17 This study found that only five patients required re-operation, which accounted to 0.08% patient-years, and there were a total of 15 valve related deaths in the subset of patients who had an aortic valve replacement. 17 Another study from Spain demonstrated that that patients with Sorin Bicarbon used for their aortic valve had over a 93% event free survival at 24 months.…”
Section: Mechanical Heart Valvesmentioning
confidence: 71%
“…17 This study found that only five patients required re-operation, which accounted to 0.08% patient-years, and there were a total of 15 valve related deaths in the subset of patients who had an aortic valve replacement. 17 Another study from Spain demonstrated that that patients with Sorin Bicarbon used for their aortic valve had over a 93% event free survival at 24 months. 67 Overall, Sorin mechanical valves have been consistently shown to have excellent in vitro functionality and favorable clinical outcomes.…”
Section: Mechanical Heart Valvesmentioning
confidence: 71%
“…Finally, the whole study was focused on the Sorin Bicarbon Fitline Bileaflet (size 25 mm). This specific device was chosen because of its widespread use [26,27]. Yet, the MPDS in its current version could be applied only to the detection of PMVT in recipients of this specific device.…”
Section: Limitationsmentioning
confidence: 99%